(untitled) (Third Sector Social Economic Review, 2017)
Digital surveillance, based on the collection and monitoring of personal information for individuals through technological means, destroys the perception of time and space with the support of technology and permeates every aspect of life. The technology that leads to the reduction of surveillance to vehicles and the deployment of these devices to human life make the inquiries about the surveillance worthless. The existence of technology in the life of the individual makes social changes possible by creating a convenient ground for changing or restructuring cultural values in a society. These changes can lead to a society being transformed into a surveillance society, and thus being called the surveillance society. In the formation of this new society, the role of visual surveillance technologies, which enable surveillance to be recognized, is so important that it cannot be denied. Indeed, visual surveillance technologies have transformed into a desire to be seen the discomfort seen. Thus, besides sharing thoughts, feelings, and dreams with other individuals, the individual also shares the places he goes to, the food he eats, the activities and activities he participates in through the new media. This creates a way for person to make self-surveil. Especially the intelligence agencies, other national and international organization can be knowledgeable through sharings of the individual in the new media networks about individuals’ needs, expectations, consumption, habits, approach to problems, ideology. In addition, changes made by visual surveillance technologies, especially communication and information technologies, transforming societies into a new society.